Comparison of photocell and stopwatch time in a 20 meter sprint: A case study of a non-trained analyst - Ivo Loureiro; Ruben Moreira; Ruben Silva; João Sampaio; Tiago Teixeira; Rodrigo Lourenço; Luís Branquinho; Pedro Flores; Alvaro Fortunato; Pedro Forte (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2023)
The purpose of the study. Running speed represents a global marker of individual performance and provides a simple method of objective measurement of motor performance for use in clinical and research environments. Speed is most often at relatively short distances at normal or fast pace, using methods of obtaining manual time (e.g., stopwatch) or automated (e.g., photocells). Materials and methods. The sample consisted of 25 students, 12 males and 13 females, all 13 years old and walked a course 20 meters away, we used to obtain the time elapsed the time, and the method by photocells. The agreement was examined using Bland and Altman graphs and linear regression. Results. There are significant and strong differences between the evaluation methods (T =14,205; p<0,001) and there is a significant and strong correlation between the variables (r = 0.902; p<0.001). Conclusions. This study suggests that for measurement in research context or in sports aimed at high yield it is advisable to use photocell, and the use of the timing method for recreational use.